Was Lysenko (partly) right? Michurinist biology in the view of modern plant physiology and genetics - Flegr, Jaroslav (Rivista di biologia, 2002)
Soviet Lysenkoism was the darkest period of modern science, and its main product--Michurinist biology--was a collection of absurd theories usually based on anecdotal observations or on a few badly designed experiments without proper controls and without any statistical evaluation of results. However, in the thirties and early forties, Lysenkoists also described (and misinterpreted) some interesting data and observations which could have been real and which might inspire modern biologists to construct testable hypotheses and suggest experiments that could extend our scientific knowledge. Here, I attempt to present an explanation in terms of modern biology of some of those phenomena, namely vegetative hybridization, wobbled heritability, heritability of environmentally induced adaptive modifications and effects of intravariety hybridization of self-fertilizing cultivars. The first two phenomena can be explained on the basis of visualization of hidden genetic and epigenetic polymorphism (originating from somatic mutations, somatic recombination and paramutations), the third phenomenon by the occurrence of intraindividual selection of somatic cell lines, and the fourth phenomenon by low heritability of phenotypic properties (and therefore also low capability to evolve) of outcrossing organisms (in comparison with self-fertilizing or asexual organisms), i.e., by a theory of frozen plasticity.
Keywords: životní prostředí; Hybridization, Genetic; hybridizace genetická; Plant Physiological Phenomena; Plants; Environment; rostliny; fyziologie rostlin